Advances in the Management of Heart Failure with Reduced Ejection Fraction; The Role of SGLT2is, ARNI, Myotropes, Vericiguat, and Anti-inflammatory Agents: A Mini-review - Vrachatis, Dimitrios A.; Papathanasiou, Konstantinos A.; Giotaki, Sotiria G.; Raisakis, Konstantinos; Kaoukis, Andreas; Kossyvakis, Charalampos; Theodorakis, Andreas; Pediotidis, Stauros; Avramides, Dimitrios; Siasos, Gerasimos; Deftereos, Spyridon (Current Pharmaceutical Design, 2023)
Heart failure with reduced ejection fraction (HFrEF) has been associated with poor prognosis, reduced quality of life, and increased healthcare expenditure. Despite tremendous advances in HFrEF management, reduced survival and a high rate of hospitalization remain unsolved issues. Furthermore, HFrEF morbidity and economic burden are estimated to increase in the following years; hence, new therapies are constantly emerging. In the last few years, a series of landmark clinical trials have expanded our therapeutic armamentarium with a ground-breaking change in HFrEF-related outcomes. Sodium-glucose co-transporter 2 inhibitors (mainly dapagliflozin and empagliflozin) have already revolutionized the management of HFrEF patients via a significant reduction in cardiovascular mortality and heart failure hospitalizations. Furthermore, vericiguat and omecamtiv mecarbil have emerged as promising and novel disease-modifying therapies. The former restores the impaired cyclic guanosine monophosphate pathway, and the latter stimulates cardiac myosin without marked arrhythmogenesis. Both vericiguat and omecamtiv mecarbil have been shown to reduce heart failure admissions. Sacubitril/valsartan is an established and effective therapy in HFrEF patients and should be considered as a replacement for angiotensin-converting enzyme inhibitors (ACEi) or angiotensin II receptor blockers (ARBs). Lastly, inflammasome activity is implicated in HFrEF pathophysiology, and the role of anti-inflammatory agents in HFrEF trajectories is readily scrutinized, yet available therapies are ineffective. This mini-review summarizes the major and most recent studies in this field, thus covering the current advances in HFrEF therapeutics.
Keywords: vericiguat